Structural and photoluminescence properties of nanostructured zinc oxide synthesized by immersion method / Azlinda Ab. Aziz - Ab. Aziz, Azlinda (2016)
In this present work, Zinc oxide (ZnO) nanostructures on gold-coated silicon (Si) substrate were prepared from zinc nitrate hexahydrate (Zn(N03)2.6HO) and urea (CH4N2O) using a low-temperature solution-immersion method. High hierarchical structure of ZnO with high surface area were successfully synthesised by the immersion method through optimization of the reaction parameters, such as different substrate surface, alignment of substrate, concentration of precursor, ratio of stabiliser in solution, and different heat temperature. FESEM, EDX, XRD, AFM and PL were the selected characterization tools to analyse the morphological, structural, surface analysis and optical properties of ZnO nanostructures. FESEM images revealed that ZnO flowerlike microspheres consist of nanosheets was the dominant structure growth along synthesis parameter. The results give evidence that the smallest diameter -11-13 |um of ZnO micro-flowers was successfully formed on gold-coated Si substrate, and gold served as a nucleation sites for the growth of ZnO micro-flowers. Low average surface roughness of ZnO nanostructures had shown the uniformity of particles size on gold-coated Si surface.